The effects of mouthwashes on the color stability of resin-based restorative materials = Efecto de los enjuagues orales en la estabilidad del color de materiales restauradores a base de resina - Ertürk Avunduk, Ayşe Tuğba; Aksu, Seçkin; Delikan, Ebru (2021)
Objective: This study investigated the effects of three types of mouthwash on the color stability of three resin-based restorative materials (nanohybrid resin composite, sonic-activated bulk-fill material, and compomer). Materials and Methods: To this end, 120 cylindrical disc specimens were prepared and polished, after which they were incubated in distilled water for 24 hours for post-polymerization. The baseline color values of each specimen were measured with a spectrophotometer, then the specimens were randomly divided into four groups. Following immersion in the mouthwashes for 24 hours, the specimens were rinsed with distilled water and dried before the color measurement was repeated. The values of color change (ΔE00) were subsequently calculated. A two-way analysis of variance and Duncan's post hoc multiple comparison tests were conducted to determine statistically significant differences among the restorative materials. Results: All samples showed discoloration after immersion, albeit some instances of discoloration were imperceptible. In this respect, a statistically significant difference was found among the restorative materials and mouthwashes (p<0.05). Imperceptible ΔE00 values were derived on the nanohybrid resin composite and compomer, but perceptible and acceptable ΔE00 values were detected on the sonic-activated bulk-fill materials (p<0.05). The clinically unacceptable discoloration was observed on the sonic-activated bulk-fill composite immersed in Listerine®. Conclusions: Clinicians should make recommendations based on the potential staining capacity of mouthwashes prescribed for daily use in restorative materials. In this way, the need for renewal of restorations due to discoloration could be avoided.
Objetivo: Este estudio investigó los efectos de tres tipos de enjuague bucal en la estabilidad del color de tres materiales de restauración a base de resina (resina nanohíbrida, resina bulk-fill de activación sónica y compómero). Materiales y Métodos: Para ello se prepararon y pulieron 120 muestras de discos cilíndricos, después de lo cual se incubaron en agua destilada durante 24 horas pospolimerización. Los valores de color de base de cada muestra se midieron con un espectrofotómetro, después las muestras se dividieron aleatoriamente en cuatro grupos. Tras la inmersión en los enjuagues bucales durante 24 horas, los especímenes se enjuagaron con agua destilada y se secaron antes de repetir la medición del color. Posteriormente se calcularon los valores de cambio de color (ΔE00). Se llevó a cabo un análisis bidireccional de la varianza y las pruebas de comparación múltiple post hoc de Duncan para determinar las diferencias estadísticamente significativas entre los materiales de restauración. Resultados: Todas las muestras mostraron decoloración después de la inmersión, aunque algunos casos esta fue imperceptible. Se encontró una diferencia estadísticamente significativa entre los materiales de restauración y los enjuagues bucales (p<0,05). Se obtuvieron valores imperceptibles de ΔE00 en el compuesto de resina nanohíbrida y el compómero, pero se detectaron valores perceptibles y aceptables de ΔE00 en la resina bulk-fill activada sónicamente (p<0,05). Se observó una decoloración clínicamente inaceptable en la resina bulk-fill activada sónicamente inmersa en Listerine®. Conclusiones: Los clínicos deben hacer recomendaciones basadas en la capacidad potencial de coloración de los enjuagues bucales prescritos para uso diario en los materiales de restauración. De esta manera, se podría evitar la necesidad de renovar las restauraciones debido a la decoloración.
En revista Odóvtos, vol. 23, no.1 (enero-abril 2021)
Descripción basada en el contenido visto el 28 de octubre, 2024
También disponible en formato HTML y EPUB